Six sigma for technical processes : an overview for R & D executives, technical leaders, and engineering managers - Creveling, Clyde M., 1956- (Prentice Hall Six Sigma for innovation and growth series., 2006)
"To sustain growth and profitability, companies must tightly align product development and commercialization to fast-changing customer requirements. In this book, Clyde Creveling identifies the four process areas most crucial to doing so - and shows executives and managers how to optimize each of them." "Creveling introduces a Six Sigma-enabled workflow that encompasses strategic product/technology portfolio definition and development, research and technology development (R & TD), tactical design engineering processes for commercialization, and operational production and service support. He presents tools, methods, and best practices for selecting the right projects, prioritizing them, and executing them rapidly, consistently, and successfully."--Jacket.